The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11356-014-3905-5
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of sulfonamide-, tetracycline-, plasmid-mediated quinolone- and macrolide-resistance genes in livestock feedlots in Northern China

Abstract: Antibiotic resistance genes (ARGs) in livestock feedlots deserve attention because they are prone to transfer to human pathogens and thus pose threats to human health. In this study, the occurrence of 21 ARGs, including tetracycline (tet)-, sulfonamide (sul)-, plasmid-mediated quinolone (PMQR)- and macrolide-resistance (erm) genes were investigated in feces and adjacent soils from chicken, swine, and cattle feedlots in Northern China. PMQR and sul ARGs were the most prevalent and account for over 90.0 % of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(43 citation statements)
references
References 40 publications
6
30
1
4
Order By: Relevance
“…Macrolide antibiotics, such as erythromycin and tylosin, are often administered together with lincosamides and streptogramins in livestock production [82,83]. Tylosin is not completely metabolized in the gut and up to three quarters of the antibiotic can be excreted in the urine and feces [84]; tylosin residues were reported in swine manure [83,84].…”
Section: Antibiotics and Antimicrobial Resistance Genes In Manurementioning
confidence: 99%
See 1 more Smart Citation
“…Macrolide antibiotics, such as erythromycin and tylosin, are often administered together with lincosamides and streptogramins in livestock production [82,83]. Tylosin is not completely metabolized in the gut and up to three quarters of the antibiotic can be excreted in the urine and feces [84]; tylosin residues were reported in swine manure [83,84].…”
Section: Antibiotics and Antimicrobial Resistance Genes In Manurementioning
confidence: 99%
“…macrolide resistance [86]. Several studies report erm genes in manured soil [82,[87][88][89][90]. Swine manure seems to have a higher content of erm genes than bovine manure samples [85], and a high diversity.…”
Section: Antibiotics and Antimicrobial Resistance Genes In Manurementioning
confidence: 99%
“…Manure carrying antibiotic resistance genes (ARGs) can enter soil, following direct land application (Fang et al, 2015). Many studies have shown that the diversity and abundance of ARGs in soil with long-term application of livestock manure has increased significantly (Ji et al, 2012;Chen et al, 2016), and ARGs in farmland have also increased significantly (Wang et al, 2014;Mu et al, 2015). Therefore, the removal of ARGs from swine manure has emerged as an environmental issue before its application to soil.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this might contribute to the stability of oqxB during the composting. qnrD and aac(6')-Ib are also located on plasmids but their variations were different from that of oqxB, probably because that oqxB is located on larger plasmids which may limit their dissemination between different species or general of bacteria [27] , while unlike oqxB, qnrD and aac(6')-Ib are often located on smaller plasmids that could propagate by the active microbial activities during composting [42,43] .…”
Section: Behaviors Of the Quinolone Resistance Genesmentioning
confidence: 95%
“…Thirteen ARGs, including five TRGs (i.e., tetC, tetG, tetX, tetM, tetO), two SRGs (i.e., sul1 and sul2), four QRGs (i.e., gyrA, qnrD, aac(6')-Ib and oqxB), two MRGs (i.e., ermB and ermF), as well as the 16S rRNA genes, were quantified using the q-PCR method. Primers used for each gene in this study were according to our former study [16] and other studies [26][27][28][29][30] . The temperature program consisted of initial denaturation at 95°C for 30 s, followed by 40 cycles of 15 s at 95°C, 20 s at different annealing temperatures and extension at 72°C for 30 s, and finished with melt-curve analysis from 60°C to 95°C.…”
Section: Dna Extraction and Quantitative Pcr (Qpcr)mentioning
confidence: 99%